2013
DOI: 10.2106/jbjs.l.01483
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk After Use of Recombinant Bone Morphogenetic Protein-2 for Spinal Arthrodesis

Abstract: A high dose of 40 mg of rhBMP-2/CRM in lumbar spinal arthrodesis was associated with an increased risk of new cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
151
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(155 citation statements)
references
References 24 publications
1
151
0
3
Order By: Relevance
“…BMP2 can promote cancer growth and metastases in gastric cancer (29), and carcinogen exposure induces BMP2 expression in the breast, resulting in stem cell transformation (30). Although controversial, use of the high dose recombinant BMP2 in patients has been linked with increased cancer rates (31)(32)(33). In contrast, loss of BMP signaling via BMP receptor mutations/deletion is associated with increased tumorigenesis and metastasis (34,35).…”
Section: Cd1333mentioning
confidence: 99%
“…BMP2 can promote cancer growth and metastases in gastric cancer (29), and carcinogen exposure induces BMP2 expression in the breast, resulting in stem cell transformation (30). Although controversial, use of the high dose recombinant BMP2 in patients has been linked with increased cancer rates (31)(32)(33). In contrast, loss of BMP signaling via BMP receptor mutations/deletion is associated with increased tumorigenesis and metastasis (34,35).…”
Section: Cd1333mentioning
confidence: 99%
“…86 Data from a multicenter, RCT of patients undergoing posterolateral fusions with BMP-2 did show a higher incidence of carcinoma among patients with BMP-2 treatment than those with autograft control. 87 Of note, multiple investigators have studied the link between BMP-2 and the incidence of cancer in large-scale studies and have not been able to replicate these findings. [88][89][90][91] Of note, most studies are limited by long-term follow-up.…”
Section: Risk Of Tumor Formation With Bmp-2mentioning
confidence: 99%
“…Pancreatic cancer was the only neoplasm that had a higher incidence in patients exposed to BMP. A recent study found a significant increase in cancer events after BMP exposure 7 . Of note, nine of the twenty cancer events in the BMP group were basal cell carcinoma or squamous cell carcinoma, which are non-SEER cancer types and frequently affect multiple sites.…”
mentioning
confidence: 96%